The Teacher's Strategies in Overcoming Student Discipline Issues at SMP M 57 Medan - Huda, Nurul; Tungkir, Abdul Rasyid; Frengky, Ridho; Rahmah, Siti (Yayasan Rahmat Islamiyah, 2025)
This study explores the strategies employed by teachers in overcoming student discipline issues at SMP M 57 Medan. Discipline problems in schools are common and can affect the learning environment, making it essential for teachers to apply effective strategies to manage and reduce disruptive behavior. This research aims to identify the approaches and methods teachers use to maintain discipline, create a positive classroom environment, and improve student behavior. Through interviews and observations, the study reveals that teachers at SMP M 57 Medan utilize a combination of preventive measures, consistent enforcement of rules, and restorative practices to address discipline issues. The results suggest that teacher-student relationships, clear expectations, and active involvement in the students’ social-emotional development are crucial components of an effective discipline strategy.